2014
DOI: 10.1016/j.juro.2014.01.097
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery Protocol after Radical Cystectomy for Bladder Cancer

Abstract: Our enhanced recovery after surgery protocol expedites bowel function recovery and shortens hospital stay after RC and urinary diversion without an increase in the hospital readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(142 citation statements)
references
References 27 publications
5
130
1
6
Order By: Relevance
“…219,220 With respect to preoperative nutrition, up to 33% of urology patients undergoing surgery are at nutritional risk. 221 Preoperative malnutrition independently increases the mortality rate, 222 but its impact on morbidity has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…219,220 With respect to preoperative nutrition, up to 33% of urology patients undergoing surgery are at nutritional risk. 221 Preoperative malnutrition independently increases the mortality rate, 222 but its impact on morbidity has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating an enhanced recovery protocol following radical cystectomy, Daneshmand et al [25] found a higher minor complication rate in patients ≥75 years old [26] used the Swedish National Patient Register to identify 7608 patients who underwent radical cystectomy between 1964 and 2008 and identified all patients who required hospitalization following radical cystectomy. After stratifying by diversion type, they found that patients who received an orthotopic neobladder were at higher risk of urinary tract infection/septicemia requiring hospitalization than those who received an ileal conduit HR 1.21 (95 % CI 1.04-1.41).…”
Section: Complicationsmentioning
confidence: 99%
“…19 ERPs have brought about a dramatic improvement in perioperative care, with a resultant positive impact on LOS. [12][13][14] Specialities and institutions have adopted variations of ERP to suit their needs; however, the mainstay of an ERP involves early mobilization, recommencement of diet, and conversion to oral analgesia in an effort to reduce morbidity and improve recovery. Successful ERPs need active collaboration between multidisciplinary team members on the ward supporting patient recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…11 Enhanced recovery pathways (ERPs) have remarkably improved postoperative LOS. 12,13 ERPs define patients' inhospital recovery with set parameters not limited to mobilization, diet, and analgesia.…”
Section: Introductionmentioning
confidence: 99%